In vivo functions of the Saccharomyces cerevisiae Hsp90 chaperone - Nathan, Debra F. (The National Academy of Sciences of the USA, 1997)
In the highly concentrated environment of the cell, polypeptide chains are prone to aggregation during synthesis (as nascent chains await the emergence of the remainder of their folding domain), translocation, assembly, and exposure to stresses that cause previously folded proteins to unfold. A large and diverse group of proteins, known as chaperones, transiently associate with such folding intermediates to prevent aggregation, but in many cases the specific functions of individual chaperones are still not clear. In vivo, Hsp90 (heat shock protein 90) plays a role in the maturation of components of signal transduction pathways but also exhibits chaperone activity with diverse proteins in vitro, suggesting a more general function. We used a unique temperature-sensitive mutant of Hsp90 in Saccharomyces cerevisiae, which rapidly and completely loses activity on shift to high temperatures, to examine the breadth of Hsp90 functions in vivo. The data suggest that Hsp90 is not required for the de novo folding of most proteins, but it is required for a specific subset of proteins that have greater difficulty reaching their native conformations. Under conditions of stress, Hsp90 does not generally protect proteins from thermal inactivation but does enhance the rate at which a heat-damaged protein is reactivated. Thus, although Hsp90 is one of the most abundant chaperones in the cell, its in vivo functions are highly restricted.